2018 Proceedings of the International Conference on Trauma Surgery Technology in Giessen - Bosbach, Wolfram A; Wilkinson, Christopher; Mieczakowski, Anna; Bagherifard, Sara; Ismat, Abdullah; López, Carolina Diana; Mele, Elisa; Muelke, Matthias; Weisweiler, David; Boecker, Wolfgang; Lips, Katrin; El Khassawna, Thaqif; et al. (Apollo - University of Cambridge Repository, 2018)
The overarching goal of the gathering was to define a concept for technology design research in Giessen to improve patient outcomes through the design of assistive technology that assists both patients and surgeons. The emerging field of regenerative rehabilitation where trauma patients are treated by methods of regenerative medicine promises great improvements for our field, but clinical success is yet to be realised. The symposium was specifically organised to acknowledge and address these issues.